2017
DOI: 10.1111/cmi.12810
|View full text |Cite
|
Sign up to set email alerts
|

Modelling persistentMycoplasma pneumoniaeinfection of human airway epithelium

Abstract: Mycoplasma pneumoniae is a human respiratory tract pathogen causing acute and chronic airway disease states that can include long-term carriage and extrapulmonary spread. The mechanisms of persistence and migration beyond the conducting airways, however, remain poorly understood. We previously described an acute exposure model using normal human bronchial epithelium (NHBE) in air-liquid interface culture, showing that M. pneumoniae gliding motility is essential for initial colonisation and subsequent spread, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 53 publications
1
37
0
Order By: Relevance
“…To our knowledge, only a few studies mainly Chinese studies have reported of the effective and well-tolerated BLT and bronchoscopy ndings such as mucus plugs on the early stage of RMPP [14,17,[26][27][28] . It has been reported that airway hypersecretion, epithelial desquamation, and remodeling cause AO in a human airway epithelium model with M. pneumoniae infection [29] . MP induces airway mucus hypersecretion by modulating the STAT/EGFR-FOXA2 signaling pathways [30] .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only a few studies mainly Chinese studies have reported of the effective and well-tolerated BLT and bronchoscopy ndings such as mucus plugs on the early stage of RMPP [14,17,[26][27][28] . It has been reported that airway hypersecretion, epithelial desquamation, and remodeling cause AO in a human airway epithelium model with M. pneumoniae infection [29] . MP induces airway mucus hypersecretion by modulating the STAT/EGFR-FOXA2 signaling pathways [30] .…”
Section: Discussionmentioning
confidence: 99%
“…This likely interplay between P1 adhesin complexes and sialic acids having diverse linkages and presentations on airway epithelium could have a profound impact on mycoplasma localization and mobilization in different regions of the conducting airways, depending on the relative abundance of each sialyl linkage. To illustrate, M. pneumoniae attaches to the tips of cilia on NHBE cells, migrates rapidly to the base of the cilia, spreads laterally more slowly, localizing to intercellular junctions, and invades the basolateral compartment (Prince et al, ). The local receptor environment, specifically the relative abundance of oligosaccharide receptors that support or are barriers to adherence and gliding, could account for this colonization pattern.…”
Section: Discussionmentioning
confidence: 99%
“…of cilia on NHBE cells, migrates rapidly to the base of the cilia, spreads laterally more slowly, localizing to intercellular junctions, and invades the basolateral compartment (Prince et al, 2014(Prince et al, , 2017. The local receptor environment, specifically the relative abundance of oligosaccharide receptors that support or are barriers to adherence and gliding, could account for this colonization pattern.…”
Section: Discussionmentioning
confidence: 99%
“…pneumoniae by the biofilm mode of growth in vivo unclear. Moreover, the interplay between pathogen and host cell has been studied in the context of an acute infection [10] as well as a chronic infection [11], but neither study investigated the roles that the biofilm lifestyle plays during infection.…”
Section: Introductionmentioning
confidence: 99%